The influence of Natural Certainty Contract (NCC) and Natural Uncertainty Contract (NUC) financings on the financial sustainability of Islamic commercial banks in Indonesia - Fitriawati, Deva Ayu; Oktaviana, Ulfi Kartika (Universitas Islam Indonesia, 2024)
IntroductionResearch on Islamic banking in Indonesia has extensively addressed its performance and stability. However, studies on stability from the perspective of Natural Certainty Contract and Natural Uncertainty Contract financing have been relatively scarce.ObjectivesThis study measures how profitability mediates the impact of Natural Certainty Contract (NCC) financing and Natural Uncertainty Contract (NUC) financing on financial sustainability.MethodThe research utilizes secondary data obtained from quarterly reports for the periods I-IV of 2018-2022 on the official website of Sharia commercial banks. All Sharia commercial banks in Indonesia listed in the OJK for the period 2018-2022 constitute the population for this study, while the sample consists of Sharia commercial banks in Indonesia that meet the criteria. The sampling method employed is purposive sampling, resulting in eight Sharia commercial banks in Indonesia as the sample based on predetermined criteria.ResultsThe findings of this study indicate that NCC financing negatively influences profitability, NUC financing has no impact on profitability, NCC financing positively influences financial sustainability, NUC financing negatively influences financial sustainability, profitability (ROA) positively influences financial sustainability, NCC financing indirectly negatively affects financial sustainability through profitability, and NUC financing indirectly has no impact on financial sustainability through profitability.ImplicationsIslamic commercial banks should be more selective in financing allocation, focusing on options with lower risks. Furthermore, Islamic commercial banks should also manage financing effectively to minimize existing risks, thereby enhancing profitability.Originality/NoveltyThis study contributes to enrich studies in the field of Islamic finance with emphasize on Islamic commercial banks profitability and financial sustainability.